Silent Trace Eliminates Differential Eyeblink Learning in Abstinent Alcoholics - Regina E. McGlinchey (International Journal of Environmental Research and Public Health, 2009)
Chronic alcoholism has profound effects on the brain, including volume reductions in regions critical for eyeblink classical conditioning (EBCC). The current study challenged abstinent alcoholics using delay (n = 20) and trace (n = 17) discrimination/reversal EBCC. Comparisons revealed a significant difference between delay and trace conditioning performance during reversal (t (35) = 2.08, p < 0.05). The difference between the two tasks for discrimination was not significant (p = 0.44). These data support the notion that alcoholics are increasingly impaired in the complex task of reversing a previously learned discrimination when a silent trace interval is introduced. Alcoholics’ impairment in flexibly altering learned associations may be central to their continued addiction.